Identifying patient-level factors associated with interest in psychosocial services during cancer: A brief report. Issue 5 (3rd September 2021) - Sannes, Timothy S.; Pirl, William F.; Rossi, Joseph S.; Grebstein, Lawrence; Redding, Colleen A.; Ferszt, Ginette G.; Prochaska, James O.; Braun, Ilana M.; Yusufov, Miryam
Abstract: Objectives: Uptake of psychosocial services during cancer treatment remains relatively low. To use these services efficiently, novel approaches – based on evidence-based theory – are needed to understand cancer patients' readiness to seek psychosocial services. Guided by the transtheoretical model (TTM), we investigated individuals' readiness to use psychosocial services by assessing decisional conflict (pros/cons) and self-efficacy, which are established as the most important constructs of predicting a specific behavior. Methods: In these secondary analyses, we examined demographic and treatment-related factors in a national sample of adult cancer patients and survivors in the United States as predictors of decisional balance (pros/cons) and self-efficacy (i.e., two core TTM constructs) of engaging in psychosocial services. Participants were recruited through an online survey. In addition to examining demographic factors (age, sex, race, and marital status) as independent variables using t tests and correlations, treatment-related variables, such as having multiple cancers, type of cancer, type of treatment, and treatment setting were included. Results: Four hundred and sixty-six participants completed the survey. The sample was primarily Caucasian (79%) and female (54.7%); average age was 47.9 (SD = 14.8). While no significant relationships emerged for self-efficacy, younger age and non-Caucasian race were significantly related to greater cons of seeking psychosocial care. Finally, those with multiple cancers versus reporting only one malignancy endorsed more cons of seeking psychosocial care. Conclusions: These data highlight the importance of measuring the cons of seeking psychosocial care during cancer treatment, with younger age, non-Caucasian, and those reporting experience with multiple cancers endorsing greater cons. This may impact eventual uptake of available services. Future research should identify individuals at risk for declining services based on perceived cons of seeking psychosocial care during cancer.